SECURITY TESTING (WHITE BOX PENETRATION TESTING) PADA AUTHENTICATION SISTEM LOGIN WEBSITE - Luthfi, Amar; Nurkifli, E. Haodudin; Maulana, Iqbal (JURNAL ILMIAH INFORMATIKA, 2025)
In 2024, according to the 2024 Indonesian Cybersecurity Landscape by the National Cyber Security Agency (BSSN), Indonesia experienced a total of 330,527,636 anomalous traffic. The highest traffic occurred in December with 112,085,045 traffic, and the lowest in May with 12,273,078 traffic. The impact of this leak is very broad, causing the risk of phishing, account hijacking, identity theft, ransomware attacks on companies, and misuse of business email. Based on this background, this study aims to minimize the many attacks that occur in the cyber world, especially on website applications. By using the Security Testing method (White Box Penetration Testing). The MD5 algorithm is still effective in protecting passwords in databases from SQL injection attacks that use common username and password combinations and on websites that use PHP without JavaScript is proven safe from Cross-Site Scripting attacks.